2021
DOI: 10.22225/seas.5.1.3166.22-28
|View full text |Cite
|
Sign up to set email alerts
|

Colour and Quality of Strawberry fruit (Fragaria x ananassa Duch.) at Different Levels of Maturity

Abstract: Strawberry fruit has five levels of maturity in terms of the color of the strawberry fruit. One of the important factors that affect the fruit's resistance from mechanical damage is the level of fruit maturity. At different levels of ripeness, strawberries have different nutritional content. The strawberries used are obtained from strawberry farmers in Pancasari Village, Tabanan Regency. The level of fruit maturity analyzed was divided into five stages, namely 0, 25%, 50%, 75%, and 100% of the red fruit. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These results were consistent with the lower pH values detected in half-red strawberries compared to those of the red samples at all the harvest times ( Table 1 ). The decrease in TA with the consequent increase in pH during the ripening has been previously explained by the conversion of organic acids into sugars in the course of the respiration process [ 15 ]. The ripening stage significantly influenced TSS at each harvest time, showing higher values (13.8, 14.5 and 4.4% more in H1, H2 and H3, respectively) in red samples than in half-red ones ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with the lower pH values detected in half-red strawberries compared to those of the red samples at all the harvest times ( Table 1 ). The decrease in TA with the consequent increase in pH during the ripening has been previously explained by the conversion of organic acids into sugars in the course of the respiration process [ 15 ]. The ripening stage significantly influenced TSS at each harvest time, showing higher values (13.8, 14.5 and 4.4% more in H1, H2 and H3, respectively) in red samples than in half-red ones ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, TA resulted to be the chemical attribute more related to IR data and the IR spectra mirrored the behaviour of TA. Generally, TA decreases during ripening due to the conversion of organic acids into sugars [ 29 ], and it is an objective indicator of maturity stage. Consequently, its prediction by ATR-FTIR might be a valid solution for a fast and non-destructive assessment of the ripening stage in strawberries.…”
Section: Resultsmentioning
confidence: 99%
“…The color values of the strawberry fruit are an important quality criterion in the evaluation of the quality and ripening time (Janurianti et al, 2021; Petriccione et al, 2015). The change in color values during storage in the coated and uncoated strawberry samples was found statistically significant ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…There was a decrease in the C * value, approximately 12 units in uncoated strawberries, about 9 units in CMC‐coated strawberries, and around 6 units in strawberries coated with CMC/PSO‐0.1‐3 at the end of the storage period. It was reported that the chroma value indicates the color intensity (saturation) of the sample and the development of the dark, pigmented compounds, which tend to mask color (Athmaselvi et al, 2013; Janurianti et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation